Control Architecture of a 10 DOF Lower Limbs Exoskeleton for Gait Rehabilitation. (25th January 2013) - Koceska, Natasa; Koceski, Saso; Durante, Francesco; Zobel, Pierluigi Beomonte; Raparelli, Terenziano
This paper describes the control architecture of a 10 DOF (Degrees of Freedom) lower limbs exoskeleton for the gait rehabilitation of patients with gait dysfunction. The system has 4 double-acting rod pneumatic actuators (two for each leg) that control the hip and knee joints. The motion of each cylinder's piston is controlled by two proportional pressure valves, connected to both cylinder chambers. The control strategy has been specifically designed in order to ensure a proper trajectory control for guiding patient's legs along a fixed reference gait pattern. An adaptive fuzzy controller which is capable of compensating for the influence of the dry friction was successfully designed, implemented and tested on an embedded real-time PC/104. In order to verify the proposed control architecture, laboratory experiments without a patient were carried out and the results are reported here and discussed.